Pilot-scale two-stage constructed wetlands based on novel solid carbon for rural wastewater treatment in southern China: Enhanced nitrogen removal and mechanism - Jia, Lixia; Sun, Haimeng; Qi Zhou; Zhao, Liu; Wu, Weizhong (JOURNAL OF ENVIRONMENTAL MANAGEMENT, 2021)
Constructed wetlands (CWs) have been proved to be an alternative to the treatment of various wastewater. However, there are few studies focused on the removal performance and mechanisms of pollutants in pilot-scale CWs packed with novel solid carbon. In this study, we investigated the effect of poly-3-hydroxybutyrate-co-3hydroxyvalerate/polyacetic acid (PHBV/PLA) blends as carbon source on pollutant's transformation, microbial communities and functional genes in pilot-scale aeration-anoxic two-stage CWs for polishing rural runoff in southern China. Results showed a striking improvement of TN removal in CWs with PHBV/PLA blends (64.5%) compared to that in CWs with ceramsite (52.9%). NH4+-N (61.3-64.6%), COD (40.4-53.8%) and TP (43.6-47.1%) were also removed effectively in both two CWs. In addition, the strains of Rhodocyclaceae and Bacteroidetes were the primary denitrifiers on the surface of PHBV/PLA blends. Further, the aerobic stage induced gathering of 16 S and amoA genes and the anoxic zone with PHBV/PLA blends increased the nirS genes, which fundamentally explained the better denitrification performance in CW based on PHBV/PLA blends. Consequently, this study will provide straightforward guidance for the operation of engineering CWs packed with polymers to govern the low-C/N rural wastewater.